Principles of Rural Tourism Development in Krisik Village, East Java: The Perspectives of Local Community - Aulanni'am Aulanni'am; Anik Martinah Hariati; Manik Eirry Sawitri; Masdiana Chendrakasih Padaga; Dyah Kinasih Wuragil; Luchman Hakim (Journal of Indonesian Tourism and Development Studies, 2021)
The research aimed to identify the local community perception in Krisik Village in Blitar Regency as a fundamental aspect of rural tourism planning and development. Three points were accepted as basic principles in rural tourism development, namely acceptance of rural tourism as an alternative to rural economic machine growth, promoting indigenous knowledge as a philosophy and value of rural tourism program implementation, and strengthening community-based tourism implementation in rural tourism programs Krisik Villages. Community involvement was a crucial issue in rural tourism planning and development.Â  In the limitation of human resources, the assistance of the university to support and increase human resources capacity in rural tourism development was important.Keywords: Ecotourism, community perception, tourism planning, tourism development